Field deficiency of macro and microelements is associated with alterations in hematology, hepatic and kidney functions and electrocardiography in sheep - Emam, Rania; Ghanem, Mohamed; Abdel-Raof, Yassein; EL-khaiat, Heba; Helal, Mahmoud A.Y. (Journal of Advanced Veterinary Research, 2024)
The objective of this work was to study the impact of deficiency of certain macro and microelements on clinical, hematobiochemical and electrocardiographic changes in sheep. The survey study was carried out on a total of 300 sheep, of which 250 suffered from mineral deficiency and 50 apparent healthy were used as control. Clinical investigations of diseased sheep revealed change wool color, easily detached wool, alopecia, pale mucous membrane, and diarrhea. Clinical examination showed significant elevation (p< 0.05) of respiratory rate and heart rate. Hematological examination revealed significant (P<0.05) decrease in Hb, RBCs, WBCs and HCT, with increase in MCV, MCH. Biochemically, there was a statistically significant (P<0.05) decline in Ca, Mg, P, Cu, Zn, Se, Fe, TP and albumin, whereas ALT, ALP, LDH, cTnI, and creatinine levels increased significantly (P<0.05). Electrocardiographic examination showed different changes, including abnormal T-waves (wide and enlarged), premature ventricular depolarization and cardiac arrhythmia. It was concluded that macro- micro element deficiency is associated with clinical, biochemical, hematological and ECG alterations. In addition, they have been related to dysfunctions of internal organs including liver, heart and kidney. Therefore, it is recommended to prescribe a proper feeding management program containing the necessary macro- and micro elements for sheep flocks and do not rely only on the grazing as a main source of feed to maintain the health and production of sheep.